Penerapan Metode Drill And Practice Untuk Meningkatkan Hasil Belajar Mahasiswa Pada Mata Kuliah Dasar Akuntansi - Fithri Widyanita Yarisma (-, 2023)
Education plays a crucial role in the progress of a country in creating intelligent, high-quality, and character based human resources. Learning methods are crucial in achieving good learning outcomes. The drill and practice method is one of the learning methods that can improve learning outcomes by involving repeated exercises. This research utilized an experimental research method with a pre-experimental one-group pretesr-posttest design. The research subject were 43 students enrolled in the odd semester of the academic year 2022/2023. The drill and practice method was implemented in teaching the accounting cycles for service an trading cmopanies in the basic accounting course. Data were collected through observations and tests. The results of the analysis showed that the students performance data followed a normal distribution, with significance values of 0.0940.05 for the pretest and 0.0650.05 for the posttest. The homogenity test indicated that the data originated from a population with equal variances, with a significance value of 0.4110.05. The paired t-test showed a Sig.(2-tailed) value of 0.0000.05, leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (H1). H1 suggests a significant influence of the drill and practice method on student learning outcomes in the basic accounting course. Descriptive analysis revealed that the mean score for the pretest was 59.42, while for the posttest, it was 73.44. This indicates that the use of the drill and practice method has a substantial impact on students ability to complete the accounting cycles for services and trading companies. In conclusion, use of the drill and practice method has a significant effect on student leraning outcomes.  This method effectively enchances students mastery of the subject matter and skills in the accounting for service and trading companies